2021
DOI: 10.3174/ajnr.a7348
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Core Needle Biopsies of Head and Neck Masses: Review of 184 Cases at a Single Academic Institution, Common and Special Techniques, Diagnostic Yield, and Safety

Abstract: BACKGROUND AND PURPOSE: Percutaneous CT-guided core needle biopsies of head and neck lesions can be safely performed with vigilant planning. This largest-to-date single-center retrospective study evaluates multiple approaches with consideration of special techniques and examines the histopathologic yield. MATERIALS AND METHODS:Retrospective review of CT-guided core biopsies of head and neck lesions from January 1, 2010, to October 30, 2020, was performed. We recorded the following: patient demographics, sedati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The minor complication rate was 12.5% (2/16), including mild inflammation of the puncture site and self-limited blood-tinged sputum. Mild infection and bleeding were the most reported minor complications after image-guided biopsy in the H&N. [3][4][5][6][7][8][9][10][11] Other minor complications included vasovagal reaction, transient facial palsy, and CSF leakage, which did not occur in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The minor complication rate was 12.5% (2/16), including mild inflammation of the puncture site and self-limited blood-tinged sputum. Mild infection and bleeding were the most reported minor complications after image-guided biopsy in the H&N. [3][4][5][6][7][8][9][10][11] Other minor complications included vasovagal reaction, transient facial palsy, and CSF leakage, which did not occur in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown a diagnostic rate of CT-guided core needle biopsy of 73%-96.8% in lesions involving the H&N as a whole. [4][5][6][7] The average size of all target lesions was approximately 2.4-3.3 cm, 4-6 including superficial and lower cervical masses. For emerging infrared navigation-guided biopsy, the diagnostic rate was approximately 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation